Cost-utility and budget impact analysis of laparoscopic bariatric surgery for obesity with Type II Diabetes Mellitus in Thailand. - Prapaporn Noparatayaporn; Montarat Thavorncharoensap; Usa Chaikledkaew; Panu Looareesuwan; Prapimporn Chattranukulchai Shantavasinkul; Preeda Sumritpradit; Ammarin Thakkinstian (PLoS ONE)
Bariatric surgery is another treatment options for patients with obesity, who cannot achieve weight controlled by conservative non-surgical therapy. Although bariatric surgery provides clinical benefits for these patients, it is costly. This study aims to evaluate the cost-effectiveness of bariatric surgery, as compared to nonbariatric surgery, in patients with body mass index (BMI) ≥32.5 kg/m2 and type 2 diabetes mellitus (T2DM), and to estimate the budget impact of bariatric surgery in Thailand. Methods A Markov model was developed to estimate and compare total costs incurred and quality-adjusted life years (QALYs) gained between bariatric surgery and nonbariatric surgery over lifetime horizontal. Analysis was conducted under payer and societal perspectives. Costs and outcomes were discounted at an annual rate of 3%. The outcomes were presented as incremental cost- effectiveness ratio (ICER). Results Under payer's perspective, bariatric surgery resulted in higher total lifetime cost (676,658.39 baht vs 574,683.38 baht) and QALYs gained (16.08 QALYs vs 14.78 QALYs), as compared to nonbariatric surgery, resulting in an ICER of 78,643.02 baht/QALY. Similarly, under the societal perspective, bariatric surgery resulted in higher total lifetime cost (1,451,923.83 baht vs 1,407,590.49 baht) and QALYs gained (16.08 QALYs vs 14.78 QALYs), as compared to nonbariatric surgery. Under societal perspective, ICER was estimated at 34,189.82 baht/QALY. A 5-year budget impact analysis indicated that bariatric surgery incurred the total budget of 223,821 million baht. Conclusions At the cost-effectiveness threshold of 160,000 baht/QALY, bariatric surgery was a cost-effective strategy and should continue to be included in the benefit package for patients with obesity and T2DM.